Isolated Vascular Malformation of the Clitoris: An Uncommon Cause of Clitoromegaly - Asjad Karim Bakhteyar; Zamurrad Parveen; Sandip Kumar Rahul (Wolters Kluwer Medknow Publications, 2024)
Clitoral enlargement (clitoromegaly) due to non-hormonal causes, particularly due to vascular malformation, is rare. Only eight such cases are reported in the literature. We report an additional case of isolated vascular malformation implicating the clitoris of a young girl child and its surgical management.